Transiting (in) Shanghai: High-skilled professionals from Spain to China. Issue 1 (1st March 2019) - Masdeu Torruella, Irene; Sáiz López, Amelia
The last decade of transformations in global economy have made international migration between China and Spain increasingly popular. The ongoing developmental pathways of the two countries – with China becoming more economically prosperous and Spain struggling to deal with financial crisis – have led to more skilled workers moving from Spain to China in search of better life opportunities. This article aims to capture new mobility flows from Spain to China that involve two groups of Spanish high-skilled professionals: Chinese migrants' descendants socialized in Spain and Spanish adults born to non-Chinese Spanish families. Drawing on semi-structured interviews the article makes a comparison between these two groups in terms of the aims of migration and the working experience in Shanghai. The main reasons for moving to China, irrespective of their ethnic backgrounds, were to develop professional careers and to gain qualified experience that might prove advantageous for their future life. For them, China is a transitional space in their professional mobility. Therefore, in our study the presence of migrants' descendants in their parents' home country cannot be described by the notions of 'return migration', 'ethnic return' and 'second-generation return'.